Climate‐induced range shifts shaped the present and threaten the future genetic variability of a marine brown alga in the Northwest Pacific. (18th May 2021) - Song, Xiao‐Han; Assis, Jorge; Zhang, Jie; Gao, Xu; Gao, Han‐Gil; Duan, De‐Lin; Serrão, Ester A.; Hu, Zi‐Min
Abstract: Glaciation‐induced environmental changes during the last glacial maximum (LGM) have strongly influenced species' distributions and genetic diversity patterns in the northern high latitudes. However, these effects have seldom been assessed on sessile species in the Northwest Pacific. Herein, we chose the brown alga Sargassum thunbergii to test this hypothesis, by comparing present population genetic variability with inferred geographical range shifts from the LGM to the present, estimated with species distribution modelling (SDM). Projections for contrasting scenarios of future climate change were also developed to anticipate genetic diversity losses at regional scales. Results showed that S . thunbergii harbours strikingly rich genetic diversity and multiple divergent lineages in the centre‐northern range of its distribution, in contrast with a poorer genetically distinct lineage in the southern range. SDM hindcasted refugial persistence in the southern range during the LGM as well as post‐LGM expansion of 18 degrees of latitude northward. Approximate Bayesian computation (ABC) analysis further suggested that the multiple divergent lineages in the centre‐northern range limit stem from post‐LGM colonization from the southern survived lineage. This suggests divergence due to demographic bottlenecks during range expansion and massive genetic diversity loss during post‐LGM contraction in the south. The projected future range of S . thunbergii highlights the threat to unique gene pools that might be lost under global changes.